Student’s perception of hybrid team-based and case-based learning in undergraduate endodontics education - Lee Yuetqi; Galvin Sim Siang Lin; Rosnani Binti Mamat; Tahir Yusuf Noorani (BMC Oral Health)
Abstract Background Limited studies have explored the use of the hybrid approach combining team-based learning (TBL) and case-based learning (CBL) in dental education. This study evaluates how students perceive the hybrid TBL-CBL approach to learning endodontics and determines whether gender and ethnicity impact students’ perceptions. Methods The final-year undergraduate Bachelor of Dental Surgery (BDS) students were invited to participate in a hybrid TBL-CBL session. They were randomly divided into six groups of six to seven students, and the session was conducted by one facilitator, supported by two lecturers. At the end of the session, a 23-item questionnaire consisting of four domains (perception of effectiveness, teacher, team interaction and learning environment) and open-ended questions was distributed. Descriptive statistics were used to analyse quantitative data using IBM SPSS software version 27.0 for Mac (SPSS Inc.). Thematic analysis was used to code qualitative data. ANCOVA (Analysis of covariance) was used to evaluate the relationship between gender and ethnicity towards the students’ perception of this hybrid TBL-CBL session, with a significant difference set at P < 0.05. Results The response rate was 78% (n = 39). Mean scores for the questionnaire items ranged from 4.44 to 4.90 (SD 0.31 to 1.43), suggesting a positive perception among students towards this hybrid TBL-CBL approach to learning endodontics. Regarding the open-ended questions, students highlighted that this hybrid TBL-CBL session effectively linked them to clinical situations, enhancing critical thinking and fostering two-way communication. However, students expressed a desire for regular TBL-CBL session with more challenging cases. Conclusions The positive perception of dental students encourages the potential integration of this novel approach into the dental curriculum, moving away from didactic lectures. Future studies could consider extending the period of using hybrid TBL-CBL in teaching and learning endodontics. This should be followed by assessing the retention of knowledge for hybrid TBL-CBL sessions compared to formal lectures.